MEMBENTUK KEPRIBADIAN SEHAT (Tawaran Model Psikoterapi Islam) - Rufaidah, Any (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2005)
The progress of modern science and technology has become human being easy to reach whatever they need and they want. Nevertheless, in other hand, those progresses with their ideology, life style, effect and etc. in fact have caused the human being faraway from their surroundings, family, and even their self. Therefore, modern men try to look for the solution of this condition, one of that is religion.However, the chosen to religion is not based on pure consciousness, but only as way to escape; hence the result is not permanent. The solutions offered by religious, such as Islamic psychotherapy, also have not touched the basic problem of humanity yet, that is the consciousness, and consequently the problem solving is not maximal.Islamic psychotherapy presented in this article, which is based on principles of epistemology of hikmah muta`aliyah, is hoped be able to be Islamic psychotherapy alternative that fix the lacking. The result is not only the temporal satisfaction of soul, but a peace of life which is permanent, and also intellectual satisfaction, without ignoring the role of syari'ah.Keywords: Problem of modern men, Islamic psychotherapy, and hikmah muta`aliyah.